Analisis Kecacatan Produk dengan Metode FMEA dan FTA pada Produk Meja OKT 501 di PT. Kurnia Persada Mitra Mandiri - Angga Prasetyo Tanto; Deny Andesta; Moh. Jufriyanto (Fakultas Teknik, 2023)
In competition in the industrial world, making quality products is mandatory for companies. The quality of the goods produced must be able to meet consumer desires. The company must also ensure that the production process runs well to produce quality products with an efficient process. This company is a subsidiary of Olympic Grub which is engaged in the manufacture of household furniture with the olymplast brand. the quality control implemented by the company is still not optimal, this is evidenced by the existence of product defects during the production process. Therefore, an analysis was carried out using the Failure Mode and Effect Analysis (FMEA) method with the aim of knowing the priority of disability problems for further repairs and the Fault Tree Analysis (FTA) method to get to the root causes that influence the occurrence of defects. From the results of the study it was found that there were types of defects including short, shinkmark, flowmark, and bending with a total of 415 defects. Based on the results of the calculation of the RPN value, the highest value was found for the type of shinemark defect so that it became a top priority in carrying out repairs. Based on this analysis, a search for the root of the problem was carried out using the FTA method, where it was found that there were 3 basic events including operators who did not understand SOPs, machine technology that had not been optimized and various raw materials for making tables where each was classified into 2 root causes for Next, a draft improvement proposal is carried out. Among them are providing machine setting training activities to all production employees, making written SOP, conducting trial errors, checking materials and completeness of tools before the production process.